PETROLOGICAL AND GEOCHEMICAL CRITERIA FOR TECTONIC ENVIRONMENT OF THE CHUKCHI SEGMENT IN OKHOTSK-CHUKCHI VOLCANIC BELT - Polin V.F.; Moll-Stalcup E.J. (My University, 2001)
Comprehensive Petrological and geochemical studies of Albian, Late Senonian and Paleogene volcanogenic basalt-bearing formations of the Chukchi segment of the Okhotsk-Chukchi volcanic belt (CS OCVB) were carried out using new evidence on REE and rare-element geochemistry. Essential discrepancies in petrogeochemical and Petrological and mineralogical parameters were revealed between Cretaceous and Paleogene rocks comparable in basicity. Cretaceous volcanites display features typical of rocks from island arcs and active continental margins. Paleogene assemblages are similar to rocks of margins (comendites, alkali granites0. Paleogene basalts show signs of relationship with intraplate Neogene-Quaternary Bering Sea basalts, but differ from them in lesser “primitivity” and lower contents of thermophyle elements (Ni, Co, Cr). The evidence obtained testifies that the Cretaceous and Paleogene basalt-bearing formations of the CS OCVB developed it different geodynamics environments. Volcanites composition of the Cretaceous stages of belt development shows them to have formed in active continental margin conditions. Paleogene volcanism reflects the situation of tectonic extension (or transform margin) to show numerous evidence of the initial stages of continental rift magmatism. The process of rift origin discontinued in its early stage, probably because a new Benioff zone originated to the east of the OCVB. Appearance of volcanogenic rocks of the intraplate geochemical type in the area of the OCVB in Paleogene is indicative of geodynamic regime changes in this region at Cretaceous-Paleogene boundary.
Keywords: Albian; Senonian; Paleogene; Okhotsk-Chukchi volcanic belt; Кайнозой::Палеоген; Мезозой::Меловая::Нижний::Альбский; Cenozoic::Paleogene; Mesozoic::Cretaceous::Lower::Albian